2020
DOI: 10.1029/2019jg005605
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variations of N2O Fluxes Across the Water‐Air Interface of Mariculture Ponds in a Subtropical Estuary in Southeast China

Abstract: While aquaculture ponds are potentially important sources of atmospheric N 2 O, the magnitude and variability of N 2 O concentrations and fluxes both within and across the ponds remain poorly understood. In this study, we examined the small-scale spatial variations of dissolved N 2 O concentrations in water and N 2 O fluxes across the water-air interface from three mariculture ponds in a subtropical estuary in southeast China. Our results showed that the dissolved concentrations and diffusive fluxes of N 2 O i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…Substantial N 2 O uxes were triggered by pond draining. This nding agreed well with previous studies that observed drainage episodes as the critical period for N 2 O emission from aquaculture ponds 21,22,58 . As discussed above, abundant soil NO 3 usually generates a higher ratio of…”
Section: Impacts On N 2 O Uxessupporting
confidence: 93%
See 1 more Smart Citation
“…Substantial N 2 O uxes were triggered by pond draining. This nding agreed well with previous studies that observed drainage episodes as the critical period for N 2 O emission from aquaculture ponds 21,22,58 . As discussed above, abundant soil NO 3 usually generates a higher ratio of…”
Section: Impacts On N 2 O Uxessupporting
confidence: 93%
“…As for the N 2 O emission from aquaculture, the IPCC default emission factor and current estimates are also limited by modeling approaches using mathematic reckoning or known as indirect N 2 O data 21 . Large variations in N 2 O emission factors from aquaculture systems have been found due to the large variability in environmental conditions and yield performance of culturing species 21,22 . Previous studies reported that N 2 O production in extensively managed aquaculture ponds was limited by the high dissolved organic C (DOC) concentrations and anaerobic conditions, and the yield-scaled emission factor for N 2 O in these ponds was 7.85-time lower than the IPCC default value 17,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Air sampling at 1 m height above the water surface was conducted by means of a 50 mL gastight syringe (Bolige, Shanghai, China). The first gas sample was discarded and the second sample was stored in a 50 mL airbag (Delin, Dalian, China) (P. Yang et al., 2020). In addition, 500 mL water at 20 cm depth was collected with polyethylene bottle and used to measure NO 3 − , NO 2 − , NH 4 + , dissolved organic carbon (DOC), and total suspended particulate (TSP).…”
Section: Methodsmentioning
confidence: 99%
“…After 24 hr of oxidation, 20 mL water in serum bottle was replaced by same volume high‐purity helium to create headspace. These serum bottles were shaken at 200 rpm for 30 min to keep the balance between water and gas phases (P. Yang et al., 2020). N 2 O concentration in headspace gas was determined by gas chromatograph (GC‐2014, Shimadzu, Japan) coupled with electron capture detector (ECD).…”
Section: Methodsmentioning
confidence: 99%